1997
DOI: 10.1007/s004270050116
|View full text |Cite
|
Sign up to set email alerts
|

Homeobox genes in axolotl lateral line placodes and neuromasts

Abstract: Gene expression has been studied in considerable detail in the developing vertebrate brain, neural crest, and some placode-derived organs. As a further investigation of vertebrate head morphogenesis, expression patterns of several homeobox-containing genes were examined using whole-mount in situ hybridization in a sensory system primitive for the vertebrate subphylum: the axolotl lateral lines and the placodes from which they develop. Axolotl Msx-2 and Dlx-3 are expressed in all of the lateral line placodes. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…To our knowledge, the homeobox genes Msx2 and Dlx3 are the only previously described transcription factors expressed during neuromast and ampullary organ development in the axolotl: in the mature sense organs, both genes were reported to be expressed in the sensory receptor cells and support cells, though expression data were only shown for neuromasts (Metscher et al 1997). However, neither of these genes is expressed during neuromast or ampullary organ development in the paddlefish (M.S.M., unpublished data), suggesting they may not be conserved markers for lateral line sense organs in bony fishes.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the homeobox genes Msx2 and Dlx3 are the only previously described transcription factors expressed during neuromast and ampullary organ development in the axolotl: in the mature sense organs, both genes were reported to be expressed in the sensory receptor cells and support cells, though expression data were only shown for neuromasts (Metscher et al 1997). However, neither of these genes is expressed during neuromast or ampullary organ development in the paddlefish (M.S.M., unpublished data), suggesting they may not be conserved markers for lateral line sense organs in bony fishes.…”
Section: Discussionmentioning
confidence: 99%
“…Only five molecular markers for vertebrate ampullary organs have previously been reported: in axolotl, Dlx3 and Msx2 (Metscher et al, 1997), and in sharks, Eya4 (O'Neill et al, 2007), Sox8, and ephrinB2 (Freitas et al, 2006). Hence, Sox3 is a novel molecular marker for vertebrate ampullary organs and also the first published molecular marker for actinopterygian ampullary organs.…”
Section: Sox3 Is Expressed Throughout the Development Of Both Mechanomentioning
confidence: 99%
“…Metscher et al [1997] found that in axolotls homeobox genes Msx1 & 2 and Dlx3 are expressed in mature neuromast support cells, and Dlx3 is also expressed in mature hair cells. Interestingly, Msx2 and Dlx3 are expressed in differentiated primitive neuromasts but not in neuromast primordia [Metscher et al, 1997].…”
Section: Inductionmentioning
confidence: 99%
“…Dorsolateral placodes not only arise from the lateral walls of the hindbrain neural folds [Northcutt, 1996], but they do so in an anterior-posterior series. Metscher et al [1997] demonstrated Hox gene expression in at least one lateral line placode, and Northcutt [1996] suggested that each dorsolateral placode should have a unique pattern of Hox gene expression that could be altered by exposure to retinoic acid, which is involved with setting boundaries of Hox gene expression. Gibbs and Northcutt [2004b] have shown that when late gastrula -early neurula axolotl embryos were exposed to retinoic acid, embryos not only lost organization of their lateral line neuromasts in a dose dependent fashion, but also completely lost ampullary organs at the highest dose.…”
Section: Inductionmentioning
confidence: 99%